Aplikasi Kedai Kopi Inovatif dengan Fitur Reservasi Ruangan: Solusi Digital untuk Meningkatkan Pengalaman Pelanggan - Ginting, Hanaya Avy Genina Br; Widiono, Suyud (LPPM Universitas Mulia, 2024)
In today's digital era, the coffee shop industry faces the challenge of adapting to the evolving needs of customers. This study aims to develop an effective room reservation system for coffee shops that not only enhances the customer experience but also improves operational efficiency. The system is designed with user-specific needs in mind, including ease of access, an intuitive interface, and integration with digital payment platforms. The system development methodology employs an agile approach, allowing for quick adjustments based on user feedback and responsive iteration. During the development phase, the team focused on refining key features through direct trials and collecting both quantitative and qualitative data from users to ensure the system met their expectations. The research findings show that the implementation of this reservation system successfully reduces customer waiting time, increases satisfaction, and optimizes coffee shop resource management. With significant contributions, this study provides empirical evidence that a digital reservation system can enhance operational efficiency and customer satisfaction, offering practical insights for coffee shop owners to improve their business competitiveness in an increasingly competitive market.